ANALISIS KARAKTER TOKOH UTAMA DALAM NOVEL LOLITA KARYA VLADIMIR NABOKOV - BYL, JEIN JEYKLIN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The research is entitled â€œAnalisis Karakter Tokoh Utama dalam Novel Lolita Karya Vladimir Nabokovâ€ is a skripsi which is to fulfill of the requirements to achieve the title of Sarjana Sastra. There are two problems to answer, those are : â€œwhat are the main charactes of Humbert Humbert described in the novel and what are the factors which affect the development of the main character Humbert Humbert. The writer has focused on the dialog through the characters and narratorâ€™s description of the action in the narrative of the story. The writer used the theory of Robertâ€™s (1983) about character. In identifying and analyzing the character the writer used the theory of Welleck and Warren (1976) to describe the leading factors development of the main character. The writer also used the intrinsic approach to analyze the interrelation between the characters in the characters in the novel that is to evaluated the characters by his words, what he is thinking and doing, and from what is the author said about them. The result of this research shows that the main character has several unique characters namely imajinative, polite, posesive, clever, calm, and economical. It also shows development of the main character in the novel that is influenced by the main characterâ€™s inner factors (past, self-control, love) and the outer factors (informations and books). Â Keyword : Characters, Leading Factors, Novel Lolita. Â